Analysis of Sports Participation Characteristics in West Java Society - Sandi Arisma Cipta Perdana Ilsya; Amung Ma'mun; Nurlan Kusmaedi; Nuryadi Nuryadi; Marisa Noviyanti Fajrah Ilsya; Muhamad Fahmi Hasan (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
The participation rate in sports and the types of sports people are interested in are important as a basis for determining sports policies in West Java, because knowing the participation rates and the types of sports people are interested in provides concrete data references to follow up on sports development policies for policymakers. This research was conducted using a cross-sectional study method involving 18,450 participants and 110 SP3OR volunteers in 27 districts and cities in West Java. The instrument used was a modified IPAQ questionnaire for measuring West Java people’s participation in sports, by the Department of Youth and Sports of West Java Province. The results showed that 49.7% of respondents were active in exercising their favorable sports, including Walking 18.9%, Aerobic Gymnastics 13.4%, Football 12.3%, Cycling 11.6%, Badminton 10.4%, Volleyball 10.1%, Run 8%, Futsal 6.7%, Basketball 1.6%, Swimming 1.6%, Self Defense 1.5%, and other sports 3.5%. This study shows that residents of West Java actively participate in recreational and easy-to-do sports activities with low intensity.